2005
DOI: 10.1002/ffj.1506
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive two-dimensional GC for the analysis of citrus essential oils

Abstract: The lemon essential oil volatile fraction is considered one of the most complex amongst all citrus oils being traditionally determined by monodimensional GC. This conventional method, although providing important qualitative/ quantitative information, lacks the necessary resolving power for the separation of several critical compounds. In the past, this has been often accomplished through the employment of conventional multidimensional chromatographic methods, which can only achieve the characterization of sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 26 publications
1
25
0
3
Order By: Relevance
“…The composition of essential oils which comprised of monoterpenes, sesquiterpenes, diterpenes, ketons, alkanes and fatty acids was in accordance to Mondello et al (2005) who reported that Citrus essential oils had two components, the volatile and non volatile compounds. The volatile compounds were mainly consisted of monoterpenes and sesquiterpenes with their oxygenated derivates, whereas the non volatile compounds were aliphatic hydrocarbons, aldehydes, ketons, acids and esters.…”
Section: Discussionsupporting
confidence: 84%
“…The composition of essential oils which comprised of monoterpenes, sesquiterpenes, diterpenes, ketons, alkanes and fatty acids was in accordance to Mondello et al (2005) who reported that Citrus essential oils had two components, the volatile and non volatile compounds. The volatile compounds were mainly consisted of monoterpenes and sesquiterpenes with their oxygenated derivates, whereas the non volatile compounds were aliphatic hydrocarbons, aldehydes, ketons, acids and esters.…”
Section: Discussionsupporting
confidence: 84%
“…and accumulated in secretory or epidermis cells and also sometimes in cavities (Ahmad, 2006). Essential oil from Citrus fruit peel is the fundamental product of genus Citrus and typically isolated by distillation or solvent extraction (Mondello et al, 2005). These are the complex mixtures of about 400 compounds of which 1-15% are non-volatile whereas 85-99% is the volatile constituents (Nannapaneni et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The outer layer of orange peel consists of numerous oil-containing cells from which an oil of limonene, other terpenes, linalool, and a resinous residue can be expressed [31]. The terpene, limonene, is probably the principal sensitizer of orange peels.…”
Section: Mechanism Involving Limonene Main Sensitizer Of Orange Peelsmentioning
confidence: 99%